Analisis Daya Dukung Kawasan dan Kesesuaian Wisata Pantai Alas Samudra Wela di Kabupaten Rembang - Wati, Heni Kristina; Arifien, Moch. (Geo-Image, 2019)
Alas Samudra Wela beach tourism area can increase visitors. A very high increase in visitors can affect the carrying capacity of the existing environment. The absence of criteria for the number of visits in determining the regional carrying capacity (DDK) of Alas Samudra Wela beach tourism has become the background of this research and aims to find out the tourist suitability index (IKW) so that the environment is maintained with visitors' comfort fulfilled. The unit of analysis of this study s divided into 3 locations, namely location 1 for coastal recreation, location 2 for swimming, location 3 for mangrove tourism. The unit of analysis used is a physical condition that refers to the parameters for suitability of coastal tourism. The method used is direct measurement, observation and documentation. The analysis technique used is scoring and descriptive analysis. The results of this study that the carrying capacity there has not exceeded the capacity so that the opportunity to be developed further. Alas Samudra Wela beach tourism suitability index is 89.29%, which means that the level of suitability of the category is very suitable or highly suitable (S1).